(untitled) (International Journal of Engineering and Computer Science, 2017)
Image binarization is the procedure of separating pixel values into two parts, black as foreground and white as background. In binarization document image is converted into binary image using thresholding techniques. Many binarization algorithms have been proposed for different types of degraded document images. The main objective of image enhancement is to modify attributes of an image to make it more suitable for a given task . To remove the noise and improve the quality of the document binarization techniques are used. Thresholding is one of such binarzation technique which is used for this purpose. Thresholding is further divided into the global and local thresholding techniques. In the document with uniform contrast delivery of background and foreground, global thresholding has been found to be best technique. Local thresholding , is an approach for the situations in which single value thresholding does not yield proper result, to overcome this a hybrid approach is introduced which is a combination of local with Otsu’s thresholding.